Redistribution, production inefficiency and decentralized efficiency - Hisahiro Naito (Osaka University, Institute of Social and Economic Research (ISER), 2003)
This paper analyzes the role of production distortion for income redistribution in an international trade model. In particular, this paper examines the role of the Stolper and Samuelson effect (Stolper and Samuelson 1941) on efficient income redistribution. It first shows that production inefficiency can be a part of a Pareto-efficient tax system when there is an asymmetric information problem between the government and individuals. Second, by using the technique that Diamond and Mirrlees (1971) originally developed, this paper shows that such production inefficiency is not only Pareto-improving for a small country but also essential to achieve world-wide Pareto-efficient allocation. Those two results suggest important policy implications for commercial policies.
Keywords: H21; F13; 330; Einkommensumverteilung; Optimale Verteilung; Optimale Besteuerung; Steuerinzidenz; Faktorpreisausgleich; Pareto-Optimum; Theorie